Spatial Analysis Of The Distribution Of Basic Education Schools (first stage) In The City Of Tartous Using GIS (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study seeks to use spatial analyzing in the evaluation of the state of Tartous city. Which is the most important indicators that are measured by the spatial development in any area by offering a vision of a survey realistic andtry to extrapolate the elements of the imbalance in the spatial distribution of geographic through use modern and sophisticated and accurate methods of reductive "time and effort, which has long been an obstacle spatial development. The study of two methods statisticians are the style of the standard deviation and style closest neighbor and the study concluded that there is a defect in the spatial distribution ofprimary education . The study also "that the accumulated has been denied many of the neighborhoods of the service as the distribution was not thoughtful of where the results of the neighbor random to the presumption of service and future predictions I pointed out that the city betterment areal need extra services in some neighborhoods of the city.